Our Lord's appointed feast a short enquiry into the meaning and significance of the words "This is my Body...this is my Blood" - Deck, Norman Cathcart, 1882-1980 (Sydney, NSW Church of England Evangelical Trust)
Includes bibliographical references.
Brethren writer.
Keywords: Lord's supper; Transubstantiation -- controversial literature